The conservation of two composite Anselm manuscripts from the twelfth century: two contrasting approaches? - Gilroy, N; Honey, A (Museum Tusculanum Press, 2012)
Oxford University's Bodleian Library has recently conserved two twelfth-century composite manuscripts containing works of St. Anselm: theologian, author and Archbishop of Canterbury. The Bodleian Library held a colloquium in April 2009 to coincide with the 900th anniversary of Anselm's death, following which two manuscripts were identified as being in particular need of conservation. Funding was offered from generous private donations to enable this work to be carried out. Although the manuscripts date from a similar period each has a complex and very different binding history creating individual conservation challenges. The earliest binding incorporates fragments of fourteenth-century polyphonic music, which have been partially removed in the past resulting in structural damage to the important fifteenth-century wooden inboard binding. In the second manuscript, the question of when and why the three texts were first brought together has significant implications for Anselmian scholars. Evidence revealed on disbinding of the volume leads us closer to solving some of these questions. This joint conference paper will explore and compare the treatment of the two manuscripts, concentrating on the way in which the binding history of each has influenced our decision-making and subsequent treatment.